Carbon-based nanocoating for extended lifetime of conventional scale inhibitor squeeze treatment in sandstone reservoirs - Mohamed, D.F. (Elsevier B.V., 2022)
Scale inhibition squeeze treatment is a common practice to prevent scale deposition within the downhole utilities, valve applications, and tubular components of the oil and gas producing wells. The conventional squeeze treatment has a short lifetime due to the reservoir rocks' limited adsorption of scale inhibitors and the quick desorption rate. As a result, this process has to be repeated multiple times per year, leading to massive increases in operational costs. Carbon-based nanomaterials are known for their high specific surface area, making them an attractive coating agent to enhance the capability of rocksâ surfaces to adsorb chemicals such as scale inhibitors. In this paper, carbon-based nanomaterials of graphene nanoplatelet (GNPs) and three different types of carbon nanotubes (CNTs) are proposed as novel nanocoating to extend the lifetime of the conventional scale inhibitor squeeze treatment. A natural polymer of Gum Arab (GA) was used to graft the nanomaterials surfaces to ensure a homogeneous and stabilized coating solution. The adsorption of diethylenetriamine penta (methylene phosphonic acid) (DTPMP) scale inhibitor into GNPs and CNTs was investigated using a UVâVis spectrophotometer. Various characterization techniques such as FTIR, Raman spectroscopy, and XPS were performed to evaluate the interaction between DTPMP and the proposed nanocoating (GNPs/CNTs). Based on UVâVis results, GNPs was found to be the optimal coating agent with an adsorption capacity of 135 mg/g at ambient temperature and 114 mg/g at 96 Â°C. Its coating gets saturated with DTPMP within 1 h of interaction. Increasing the initial scale inhibitor concentration was found to increase the adsorption capacity of GNPs. Based on the core flooding conducted on Berea sandstone, the injection of nanocoating into the core sample reduces the permeability by only 12. Finally, the injected nanomaterial was safely transported through the core, and the primary retention mechanism was adsorption rather than physical filtration/plugging. Â© 2022 Elsevier B.V.